ANALISIS YURIDIS PERSYARATAN USIA BAKAL CALON PRESIDEN DAN/ATAU BAKAL CALON WAKIL PRESIDEN DALAM PEMILU 2024 (STUDI KASUS PUTUSAN MK/NOMOR-90-XXI-PUU/2023): Juridical Analysis Of Age Requirements For Presidential And Vice-Presidential Candidates In The 2024 Election (Case Study Of The Constitutional Court Decision No. 90/Xxi/Puu/2023) - Rama Mahendra; Eko Primananda (AMICUS CURIAE, 2025)
This study intends to examine Constitutional Court Decision Number 90/PUU-XXI/2023, which amended the provision of Article 169 letter q concerning the minimum age requirement for presidential and vice-presidential candidates. This study identifies problems concerning the Court’s legal considerations in the judicial review of Article 169 letter q of Law Number 7 of 2017 on General Elections, particularly related to the nomination of candidates for the 2024 Election, as well as analyzing the legal implications of the decision. The research method applied is a normative-empirical legal approach, combining field research and literature study, aimed at understanding the legal reasoning behind the Constitutional Court’s ruling. The findings indicate that there has been a direct change to Article 169 letter q, where the minimum age requirement of 40 years, previously absolute, has been expanded by adding an alternative condition, namely having previously held or currently holding an elected office, including regional head elections. With the results of the research and conclusion, it was found that this decision has significant implications for the system of presidential and vice-presidential candidacy in Indonesia, broadens opportunities for candidates from regional head backgrounds, and raises debates regarding the consistency of the principles of equality and legal certainty in elections.